High fluoride and low pH level have been detected in popular flavoured beverages in Malaysia - Rahim, Z.H.A.; Bakri, M.M.; Zakir, H.M.; Ahmed, I.A.; Zulkifli, N.A. (2014)
Objective: In children, excessive ingestion of fluoride from different sources including bottled drinking water and flavoured beverages or soft drinks can lead to the development of dental fluorosis. In addition, the pH level of beverages is important. Low pH can cause dental erosion. In this study we explore the fluoride content and pH level of certain popular beverages available in Malaysian supermarkets and hawkers’ stalls.